Successful kidney transplant from methanol-intoxicated donor: a case report - Trujillo Mauricio , Evelyn L. (2025)
The gap between supply and demand of organs available for transplant is increasing worldwide. Over the years, alternatives have been proposed, such as including donors who have died from fatal methanol poisoning. However, this idea still generates controversy and doubts due to the possibility of transmitting the methanol to the recipient or transplanting a damaged organ. Faced with the increase of methanol intoxication events in Peru and the absence of reports in our country, we present a case of a donor who died because of methanol, with a favorable evolution of the recipient, as well as the function of the kidney graft, thus corroborating the safety of transplantation in this type of donor.